2010
DOI: 10.3892/ol_00000075
|View full text |Cite
|
Sign up to set email alerts
|

Development of hepatocellular carcinoma in patients with chronic hepatitis C more than 10 years after sustained virological response to interferon therapy

Abstract: Abstract. The risk factors for the development of hepatocellular carcinoma (HCC) in patients who have achieved a long-term sustained viral response (SVR) to interferon (IFN) are not fully understood. This study aimed to investigate the characteristics of patients who developed HCC after 10 years of achieving SVR. We retrospectively studied 5 patients with HCC which developed more than 10 years after the termination of IFN therapy. The clinical characteristics at the induction of IFN therapy were male gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In experimental models, using transgenic mice, HCV core proteins showed a causative role in the development of steatosis and HCC [ 65 , 66 , 67 , 68 ]. The experimental evidence has been confirmed in the majority of clinical studies performed [ 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Both retrospective and prospective studies, with only a few exceptions, showed that HCV-related steatosis was strictly associated with the development of HCC and that the amount of fatty liver deposition was an important risk factor for HCC [ 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Hcv-associated Steatosis and Progression Of Liver Damagementioning
confidence: 69%
“…In experimental models, using transgenic mice, HCV core proteins showed a causative role in the development of steatosis and HCC [ 65 , 66 , 67 , 68 ]. The experimental evidence has been confirmed in the majority of clinical studies performed [ 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Both retrospective and prospective studies, with only a few exceptions, showed that HCV-related steatosis was strictly associated with the development of HCC and that the amount of fatty liver deposition was an important risk factor for HCC [ 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Hcv-associated Steatosis and Progression Of Liver Damagementioning
confidence: 69%
“…Furthermore, patients with SVR present an important improvement in hepatic inflammation and fibrosis, and consequently a reduction in the risk of developing HCC 3 , 14 , 17 , 18 . However, the presence of HCC in non-cirrhotic patients with SVR is possible and Asia practically monopolizes existing accounts, especially Japan 1 , 12 , 16 . The factors involved in these cases as well as the profile of these patients are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of a metaanalysis of retrospective studies, risk of HCC halves in patients with C virus infection who achieve sustained viral response (SVR) with interferon and ribavirin [3]. However, there are some reports about the development of HCC after achieving SVR [3][4][5] even 10 years after finishing antiviral treatment. HCC incidence and risk factors in these patients are not well established.…”
Section: Discussionmentioning
confidence: 96%
“…Morgan et al [10] found that in patients with SVR, risk of HCC was 7, 2, and 3 times higher in relation to age ([50 years), advanced histological stage (fibrosis score CF3), and male gender, respectively. High ALT level in relation to the presence of alcoholic steatosis, diabetes mellitus, or obesity [4] has been suggested in different studies as another risk factor for HCC. In addition, occult HBV infection has also been associated as another risk factor for HCC.…”
Section: Discussionmentioning
confidence: 98%